Methylation-driven gene DLL3 is a potential prognostic biomarker in ocular melanoma correlating with metastasis - Yang, Ludi; Wang, Gaoming; Shi, Hanhan; Jia, Shichong; Ruan, Jing; Cui, Ran; Ge, Shengfang (Frontiers in Oncology, 2022)
Background: Ocular melanoma is an aggressive malignancy with a high rate of metastasis and poor prognosis. Increasing evidence indicated that DNA methylation plays an important role in the occurrence and development of ocular melanoma. Hence, exploring new diagnostic and prognostic biomarkers at the genetic level may be beneficial to the prognosis of patients with ocular melanoma. Methods: We collected DNA methylation and gene expression profiles of human UM (uveal melanoma) and CM (conjunctival melanoma) samples from various datasets. We conducted differential methylation and expression analyses to screen the potential biomarkers. Correlation analysis was performed to investigate the relationships between the expression level of DLL3 (delta-like protein 3) and the methylation level of its corresponding CpGs. We explored the prognostic and diagnostic value of DLL3 in UM and CM. Functional annotation and GSEA (gene set enrichment analysis) were applied to get insight into the possible biological roles of DLL3. A cohort of 60 ocular melanoma patients as well as UM and CM cell lines were used to validate our findings in bioinformatic analyses. Results: We found that DLL3 was a methylation-driven gene correlating with UM metastasis. The CpGs of DLL3 are mainly located in the gene body and their methylation level positively correlated to DLL3 expression. Multivariate Cox regression analysis revealed that DLL3 was an independent protective factor for UM patients. High DLL3 expression significantly prolonged the overall survival and disease-free survival of UM patients. DLL3 also showed a promising power to distinguish CM from normal tissues. Functional annotation exhibited that DLL3 may suppress UM progression through modulating immune activities and down-regulating various signaling pathways. External datasets, biospecimens, and cell lines further validated the aberrant expression and prognostic role of DLL3 in ocular melanoma. Conclusion: Methylation-driven gene DLL3 could serve as a new potential diagnostic and prognostic biomarker in ocular melanoma. Our findings may contribute to improving the clinical outcomes of patients with UM or CM.